The Mapping of Indigenous Knowledge of People at 3T (Frontier, Outermost, and Least Developed) Regions as an Ethnoscience Study - Parmin, Parmin; Taufiq, Muhamad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
This research intended to map indigenous knowledge of people in the frontier, outermost, and least developed regions or generally referred to as 3T (Terdepan/Frontier, Terluar/Outermost, Tertinggal/Least Developed) regions. This research employed a qualitative research approach through a descriptive method in which an experimental method was performed for mapping the indigenous knowledge. The target mapping area was Papua, Aceh, West Kalimantan, and East Nusa Tenggara. Geographical position, research funding, and time allocation became the main considerations in selecting these areas. The four 3T regions are said to be the most appropriate as the locals remain to believe and apply their indigenous knowledge. The mapping results found that several indigenous knowledge is potentially tested scientifically in labs, they are Bakar Batu, Tanam Sasi, and Honai in Papua; Rumoh Aceh and Batu Nisan in Aceh; Berjuluk Baatutuk and Betang Radang in West Kalimantan; and Ebang and Welang in East Nusa Tenggara. There are numerous traditions found in the research location, yet those that do not have met the criteria of scientific objects, such as myths and legends, were not included. The mapping results were followed by confirming the opinions of prospective science teachers obtained by 85 % of 54 students who were interested in this finding as a study of ethnocentric The research concluded that the indigenous knowledge of people in 3T regions are unique and required to be further examined scientifically and could be reviewed as a source for Ethnoscience course. This research recommendation is that in science learning, especially in the 3T region should pay attention to efforts to change traditional knowledge into scientific knowledge through integrating the mapping of indigenous knowledge as the content of ethnoscience.